AYAH DALAM KARYA GRAFIS TEKNIK (LINOLEUM CUT) - Sundari S; Irwan Irwan (Universitas Negeri Padang, 2021)
The creation of this final work aims to visualize how the father's struggle to earn a living with his aging age into the form of graphic art (linoleum cut). Showcasing the various hard jobs that the father does everyday to support his family. The technique used is the relief print technique (linoleun cut). Relief print using lino rubber as a cliché and the work process used in the creation of this graphic art work goes through several stages: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Realization of the concept, (5) Completion. The results of the visualization of Father in Graphic Art Work (Linoleum Cut) are 10 works with the titles: (1) Scavenging, (2) Hoping, (3) Looking for Trash, (4) Tired, (5) Lifting Stones, (6) Enduring, (7) shouldered, (8) continued to live, (9) bowed, (10) carried the burden.Keywords: Father, Graphic Art, Linoleum Cut